2023
DOI: 10.3389/fimmu.2023.1102126
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of serum S100B in sepsis-associated encephalopathy: A systematic review and meta-analysis

Abstract: BackgroundIn sepsis, brain dysfunction is known as Sepsis-associated encephalopathy (SAE), which often results in severe cognitive and neurological sequelae and increases the risk of death. Our systematic review and meta-analysis aimed to explore the diagnostic and prognostic value of serum S100 calcium-binding protein B (S100B) in SAE patients.MethodsWe conducted a systematic search of the databases PubMed, Web of Science, Embase, Cochrane databases, CNKI, VIP, and WFSD from their inception dates until August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…S100β has also been associated with neurologic complications and worse outcomes in the ECMO population ( 32 , 33 ). A systematic review and meta-analysis suggest that serum levels of S100β protein may be a useful diagnostic and prognostic biomarker of sepsis-associated encephalopathy ( 34 ). Elevated S100β levels observed in our study likely reflect early blood-brain barrier alterations associated with sepsis and associated astrocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…S100β has also been associated with neurologic complications and worse outcomes in the ECMO population ( 32 , 33 ). A systematic review and meta-analysis suggest that serum levels of S100β protein may be a useful diagnostic and prognostic biomarker of sepsis-associated encephalopathy ( 34 ). Elevated S100β levels observed in our study likely reflect early blood-brain barrier alterations associated with sepsis and associated astrocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PI levels have been implicated in cognitive dysfunction in patients with sepsis ( 26 ). Concurrently, high expression levels of S100B are involved in neuroinflammation and have been notably associated with neurodegenerative disorders such as Alzheimer's disease and Parkinson's disease ( 27 , 28 ). Importantly, an animal study suggested that S100B emanated primarily from the brain during endotoxemia and played a pivotal role in acute brain injury and long-term cognitive impairment ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the central nervous system is injured, S100β protein escapes from the damaged cells into the cerebrospinal fluid and then into the blood through the damaged blood–brain barrier ( Michetti et al, 2019 ). Tan et al (2021) discovered that POCD development was strongly connected with postoperative S100β expression, and hence S100β protein is frequently utilized as a diagnostic for brain damage ( Hu et al, 2023 ). We discovered that the serum concentration of S100β in groups R and D was significantly lower than in group C at time points T 4 , T 5 , and T 6 , because remimazolam and dexmedetomidine attenuated the inflammatory response, inhibited astrocyte and microglia activation, decreased S100β protein release, attenuated the interaction between neurons and glial cells, and protected brain cells and neural tissue from inflammatory factors, maintains intracranial homeostasis, and played a role in brain protection ( Wang N. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%